A modified preparation method for a crystal domain petroleum coke-based silicon-carbon composite electrode material
By constructing a silicon-carbon composite electrode material with a four-stage structure of "carbon-vacuum-silicon-carbon", the problems of silicon negative electrode material in lithium-ion batteries are solved, and efficient lithium ion diffusion and stable cycling performance are achieved.
Patent Information
- Application Number
- CN202211258233.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-14
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-10-14
AI Technical Summary
In lithium-ion batteries, the volume expansion of the silicon negative electrode material during the process of lithium ions embedded and disengagement leads to material powdering and SEI film generation, which in turn affects the cycle stability and reversible capacity. At the same time, silicon has a low conductivity, which affects the diffusion of lithium ions.
Crystal Domain Petroleum Coke is used as the carbon source, and through hydrothermal reaction, magnesium thermal reduction and high-temperature carbonization, a silicon-carbon composite electrode material with a four-level structure of "carbon-vacuum-silicon-carbon". The material forms an "egg yolk-egg shell"-shaped structure by coating calcium carbonate as a sacrificial layer and an amorphous carbon layer, which alleviates the volume expansion of silicon and increases the conductivity.
It has achieved high conductivity, high reversible specific capacity, stable cycle performance and magnification performance of silicon-carbon composite electrode materials. The first circle of Coulomb efficiency is above 70%, the reversible specific capacity is above 580mAh/g at 0.1C current density, and the specific capacity is above 470mAh/g at a high current density of 10C.
Smart Images

Figure CN115425220B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion battery electrode materials and relates to a modification preparation method of a crystalline petroleum coke-based silicon-carbon composite electrode material. Background Art
[0002] In recent decades, lithium-ion batteries have been widely studied and paid attention to due to their many advantages such as high voltage, high energy, long cycle life, and no memory effect. However, graphite as an anode material has a low specific capacity and poor high-rate charge and discharge performance, which makes it difficult to meet the growing needs of mankind. Therefore, it is necessary to find materials with high energy density to replace graphite-based negative electrode materials. Silicon negative electrode has a theoretical specific capacity of up to 4200mAh / g and abundant reserves. It is entirely possible to replace graphite as a new commercial negative electrode material. However, its own volume expansion when inserting and extracting lithium ions will cause the negative electrode material to pulverize and generate SEI film, resulting in poor cycle stability and irreversible capacity loss. At the same time, silicon has a low conductivity at room temperature, making it difficult for lithium ions to diffuse in the silicon negative electrode. In order to reduce the volume effect and improve the conductivity, many strategies for designing silicon-based anode materials have been proposed, among which silicon-carbon composites are being widely studied as one of the most successful strategies. However, most of the research focuses on the structural design of silicon-carbon composites. In fact, the microstructure of the carbon component has a crucial influence on its electrochemical behavior, which further affects the battery performance.
[0003] Petroleum coke is a good carbon source for preparing high-performance silicon / carbon composite materials, and crystalline petroleum coke is a kind of petroleum coke in which needle-domain, wide-domain and mosaic polarization structures coexist and are evenly distributed and mixed. In the needle-domain and wide-domain structures of the material, the carbon layer is arranged more regularly, and has both higher lithium storage capacity and better cycle stability. The mosaic structure provides a certain chaotic layer structure after carbonization and graphitization, which is conducive to improving the rate performance of the material. The soft carbon material derived from crystalline petroleum coke has outstanding electron transfer characteristics and structural elasticity. The relative content of its different polarization structures can be conveniently adjusted by heat treatment temperature, and its crystallinity can be further regulated to achieve the adjustment of the overall electrochemical performance of the material. The properties of active silicon particles require that the surface of the carbon component has certain anchoring points for fixing. Compared with ordinary petroleum coke, most of the crystalline petroleum coke is needle-domain and wide-domain structure. After activation treatment, it can provide a sufficient number of anchoring points for active silicon particles while maintaining high lithium storage capacity and cycle performance. Therefore, the present invention uses crystalline petroleum coke as a carbon source, and prepares a silicon-carbon composite electrode material with good performance by constructing a multi-layer silicon-carbon composite structure. Summary of the invention
[0004] In order to overcome the shortcomings of the prior art, the present invention provides a modification and preparation method of a crystalline petroleum coke-based silicon-carbon composite electrode material. Petroleum coke with a crystalline structure and an oxygen-containing organic silicon compound are used to prepare a silicon-carbon composite material as the inner core through particle size screening, hydrothermal reaction, magnesium thermal reduction and high-temperature carbonization steps. Calcium carbonate and an amorphous carbon layer are then wrapped in turn on the outer layer. Finally, a "yolk-eggshell" type silicon-carbon composite electrode material with a quaternary structure of "carbon-void-silicon-carbon" is obtained through hydrochloric acid etching. The silicon-carbon composite electrode material has the advantages of good conductivity, high reversible specific capacity, stable cycle performance and good rate performance.
[0005] The object of the present invention is achieved through the following technical solutions:
[0006] A modification and preparation method of a crystal domain petroleum coke-based silicon-carbon composite electrode material comprises the following specific steps:
[0007] Step 1: using crystal domain petroleum coke as a raw material, crushing it and then sieving it with a 600-1000 mesh screen to obtain crystal domain petroleum coke particles; adding the crystal domain petroleum coke particles to an organic acid solution with a concentration of 3-5 mol / L, stirring at 180-230° C. for 24 hours to obtain activated crystal domain petroleum coke particles; the organic acid includes trichloroacetic acid or p-toluenesulfonic acid;
[0008] Step 2: Ultrasonic dispersion of activated crystalline petroleum coke particles in deionized water, then dropwise addition of oxygen-containing organosilicon compound, and continued ultrasonication until complete dispersion; transfer the dispersion to a hydrothermal reactor, and react at 160-200° C. for 6-15 hours; filter the product of the hydrothermal reaction, wash the precipitate with ethanol and deionized water three times respectively, and dry it in an oven to obtain a dried product;
[0009] Step 3: Mix the dried product with magnesium powder and place it in a stainless steel reactor, and perform magnesium thermal reaction at 600° C. for 4-8 hours under argon atmosphere; wash the product of magnesium thermal reaction with dilute hydrochloric acid, ethanol and deionized water respectively until neutral to obtain a treated magnesium thermal reaction product;
[0010] Step 4: Ultrasonic dispersion of the treated magnesium thermal reaction product in deionized water, adding sodium carbonate and calcium chloride in turn, stirring vigorously to obtain a white precipitate uniformly coated with calcium carbonate; then adding the white precipitate to a solution of isotropic asphalt, stirring for 24 hours and filtering, washing the precipitate with deionized water and drying; placing the dried precipitate in a tubular furnace, pre-oxidizing at 320°C in an air atmosphere for 2-4 hours, and carbonizing at 800-1200°C in an argon atmosphere for 2 hours to obtain a carbonized product;
[0011] Step 5: Place the carbonization product in 0.1 mol / L hydrochloric acid, wash thoroughly to remove calcium carbonate precipitate, then wash with deionized water until neutral, and dry to obtain a "carbon-void-silicon-carbon" four-level core-shell crystal domain petroleum coke-based silicon-carbon composite electrode material.
[0012] In the present invention, the polarization structure of the crystalline petroleum coke is composed of pin-domain, wide-domain and mosaic structures, wherein the pin-domain and wide-domain polarization structure sizes are 50-500 μm, accounting for 70%-85% of the total area, and the mosaic polarization structure size is 1-50 μm, accounting for 15%-30% of the total area; the three polarization structures coexist and are evenly distributed and mixed; the polarization structure size refers to the length of the monochromatic area presented by the anisotropic substance in the crystalline petroleum coke under orthogonal polarized light.
[0013] In the present invention, the oxygen-containing organosilicon compound is selected from one of triisopropylsilyl trifluoromethanesulfonate, 3-tert-butyldimethylsilyl-2-propyn-1-ol or (1,1-dimethylethyl)dimethylsilyl trifluoromethanesulfonate.
[0014] In the present invention, the silicon content of the product is controlled by the amount of oxygen-containing organosilicon compound added in the hydrothermal synthesis raw material. The more oxygen-containing organosilicon compound is added, the higher the silicon content in the final product. Preferably, the amount ratio of crystal domain petroleum coke particles, organic acid solution and oxygen-containing organosilicon compound is 1g: 200mL: (0.1-0.5)g;
[0015] The dried product obtained in step 2, magnesium powder, sodium carbonate and calcium chloride are used in a ratio of 1 g: 0.1 g: (1-1.5) g: (1.2-1.8) g;
[0016] In step 4, the ratio of white precipitate to isotropic asphalt is 1 g:(1-1.5) g.
[0017] In step 4 of the present invention, the heating rate of the air atmosphere pre-oxidation process is 1°C / min.
[0018] In the present invention, the homologous asphalt is a coal-based coated asphalt, a petroleum-based coated asphalt or a high-temperature coal tar pitch having a softening point of 100-200°C. The method for preparing a solution of the homologous asphalt is to dissolve the homologous asphalt in a solvent, wherein the solvent is selected from one or more of tetrahydrofuran, toluene, N-methylpyrrolidone and pyridine; the dosage ratio of the solvent to the homologous asphalt is 100mL:(1-1.5)g.
[0019] In the present invention, in the four-level core-shell crystal domain petroleum coke-based silicon-carbon composite electrode material of "carbon-void-silicon-carbon", the preferred silicon layer thickness is 0.1-0.2 μm, the void structure thickness is 0.3-1 μm, and the amorphous carbon layer thickness is 0.5-1 μm.
[0020] The present invention also provides a crystalline petroleum coke-based silicon-carbon composite electrode material prepared by the above method. The electrode material has a four-level core-shell structure of "carbon-void-silicon-carbon", a first-cycle coulomb efficiency of more than 70%, a reversible specific capacity of more than 580 mAh / g at a current density of 0.1C, and a specific capacity of more than 470 mAh / g at a high current density of 10C.
[0021] The present invention uses crystalline petroleum coke as a widely available carbon substrate. The crystalline petroleum coke is a petroleum coke in which needle-domain, wide-domain and mosaic polarization structures coexist and are evenly distributed and mixed, which effectively buffers the volume expansion of silicon-based materials. The carbon layers in the needle-domain and wide-domain structures are arranged regularly. Compared with ordinary petroleum coke, it has a higher lithium storage capacity, more stable cycle performance and more active sites for silicon connection. Moreover, the fewer mosaic structures distributed between the flow domain structures provide a certain chaotic layer structure after carbonization and graphitization, which is beneficial to improving the rate performance of the material. The hydrothermal reaction process allows the organic silicon to be deposited in situ on the surface of the carbon substrate to form a uniform coating layer, which promotes the close combination of the two. After magnesium thermal reduction, the silicon-coated crystalline petroleum coke is obtained; calcium carbonate is used as a sacrificial layer. Compared with the commonly used SiO2 sacrificial layer, this method avoids the use of hydrofluoric acid as an etchant, reduces the safety risk in the preparation process, and calcium carbonate is also easy to etch. The resulting void layer reserves enough space for the volume expansion of the inner silicon layer; and the outermost coated carbon layer further constrains the expansion of silicon due to the volume change of silicon during the charging and discharging process, and the obtained "carbon-void-silicon-carbon" four-level "yolk-eggshell" type composite silicon-carbon electrode material. According to the amount of oxygen-containing organic silicon compound, the amount of sodium carbonate, calcium chloride and isotropic asphalt is appropriately increased or decreased, so that the thickness of the void layer and the coated carbon layer increases or decreases when the silicon layer thickness increases or decreases, which can ensure that the performance of the prepared silicon-carbon composite electrode material reaches the optimal level. Finally, an electrode material with high reversible cycle specific capacity and stable cycle performance was prepared. The coulombic efficiency in the first cycle was above 70%, the reversible specific capacity was above 580 mAh / g at a current density of 0.1C, and the specific capacity was above 470 mAh / g at a high current density of 10C.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The carbon matrix in the composite material is crystalline petroleum coke prepared from heavy oil. As a widely available carbon substrate, crystalline petroleum coke effectively buffers the volume expansion of silicon-based materials. The needle-domain and wide-domain structural carbon layers are more regularly arranged, with higher lithium storage capacity and better cycle stability. At the same time, after activation, a large number of active sites are provided to connect with silicon. The few mosaic structures distributed between the flow-domain structures provide a certain chaotic layer structure after carbonization and graphitization, which is conducive to improving the rate performance of the material.
[0024] 2. Using calcium carbonate as a sacrificial layer avoids the use of hydrofluoric acid when SiO2 is used as a sacrificial layer, reducing the safety risks in the preparation process. Calcium carbonate is easy to etch, and the void layer after etching reserves enough space for the volume expansion of the inner silicon layer.
[0025] 3. Using isotropic asphalt to wrap a layer of amorphous carbon on the outermost layer of the material effectively constrains the volume expansion of silicon during the charging and discharging process and improves the cycle stability of the material.
[0026] 4. The carbon precursor is activated by organic acid solution to increase the oxygen-containing functional groups on the crystalline petroleum coke. At the same time, organic silicon is used as the silicon source. The interaction between the functional groups on the surface of asphalt and organic silicon promotes the combination of the two. The mixture is then reduced by a one-step magnesium thermal reaction. Compared with mechanical mixing, the combination of silicon and carbon is tighter. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The schematic diagram of the structure of the crystalline petroleum coke-based silicon-carbon composite electrode material prepared in the present invention.
[0028] Figure 2 This is a polarized photo of the crystalline petroleum coke used in the present invention. DETAILED DESCRIPTION
[0029] The modification and preparation method of the crystalline petroleum coke-based silicon-carbon composite electrode material of the present invention is described in detail below with reference to the embodiments.
[0030] Embodiment 1:
[0031] This embodiment provides a modification preparation method of a crystal domain petroleum coke-based silicon-carbon composite electrode material, comprising the following specific steps:
[0032] (1) grinding the crystal domain petroleum coke, sieving it through a 1000 mesh sieve, taking 1 g of the crystal domain petroleum coke particles and adding them into 200 mL of a 5 mol / L trichloroacetic acid solution, stirring at 200° C. for 24 h, to obtain activated crystal domain petroleum coke particles;
[0033] (2) dispersing the activated crystalline petroleum coke particles in deionized water, ultrasonicating for 1 hour, then dropwise adding 20 mL of 0.01 g / mL ethanol solution of triisopropylsilyl trifluoromethanesulfonate, and continuing ultrasonicating for 1.5 hours until completely dispersed; transferring the dispersion to a hydrothermal reactor, reacting at 160° C. for 8 hours; filtering the product of the hydrothermal reaction, washing the precipitate with ethanol and deionized water three times respectively, and drying it in an oven at 80° C. for 24 hours; obtaining a dried product;
[0034] (3) 1 g of the dried product was mixed with 0.1 g of magnesium powder and placed in a stainless steel reactor for reaction at 600 ° C for 6 h under argon atmosphere. The product was then washed with 0.5 mol / L dilute hydrochloric acid, ethanol and deionized water until neutral, and vacuum dried at 100 ° C for 24 h to obtain a treated magnesium thermal reaction product;
[0035] (4) Ultrasonic dispersion of the treated magnesium thermal reaction product in deionized water, adding 1.4 g of sodium carbonate and 1.6 g of calcium chloride in turn, stirring vigorously to obtain a white precipitate uniformly coated with calcium carbonate; completely dissolving 1.4 g of high-temperature coal tar pitch in 100 mL of toluene to obtain a solution of isotropic asphalt, adding 1 g of white precipitate to the solution, stirring for 24 h and then filtering, washing the precipitate with deionized water and drying; placing the dried precipitate in a tubular furnace, pre-oxidizing at 320° C. in an air atmosphere for 2 h, and carbonizing at 1000° C. in an argon atmosphere for 2 h to obtain a carbonized product; wherein the heating rate during the pre-oxidation process is 1° C. / min;
[0036] (5) The carbonized product is placed in 0.1 mol / L hydrochloric acid, washed thoroughly to remove calcium carbonate precipitate, then washed with deionized water until neutral, and dried to obtain a "carbon-void-silicon-carbon" four-level core-shell crystal domain petroleum coke-based silicon-carbon composite electrode material A; wherein the thickness of the silicon layer is 0.1 μm, the thickness of the void structure is 0.5 μm, and the thickness of the amorphous carbon layer is 0.7 μm.
[0037] Embodiment 2:
[0038] This embodiment provides a modification preparation method of a crystal domain petroleum coke-based silicon-carbon composite electrode material, comprising the following specific steps:
[0039] (1) grinding the crystal domain petroleum coke, sieving it through an 800-mesh sieve, taking 1 g of the crystal domain petroleum coke particles and adding them into 200 mL of a 5 mol / L p-toluenesulfonic acid solution, activating and stirring them at 200° C. for 24 h, and obtaining activated crystal domain petroleum coke particles;
[0040] (2) dispersing the activated crystalline petroleum coke particles in deionized water, ultrasonicating for 1 hour, then dropwise adding 30 mL of 0.01 g / mL ethanol solution of triisopropylsilyl trifluoromethanesulfonate, and continuing ultrasonic dispersion for 1.5 hours until completely dispersed; transferring the dispersion to a hydrothermal reactor, reacting at 160° C. for 8 hours; filtering the product of the hydrothermal reaction, washing the precipitate with ethanol and deionized water three times respectively, and drying it in an oven at 80° C. for 24 hours; obtaining a dried product;
[0041] (3) 1 g of the dried product was mixed with 0.1 g of magnesium powder and placed in a stainless steel reactor for reaction at 600 ° C for 6 h under argon atmosphere. The product was then washed with 0.5 mol / L dilute hydrochloric acid, ethanol and deionized water until neutral, and vacuum dried at 100 ° C for 24 h to obtain a treated magnesium thermal reaction product;
[0042] (4) Ultrasonic dispersion of the treated magnesium thermal reaction product in deionized water, and sequentially adding 1.4 g of sodium carbonate and 1.6 g of calcium chloride, stirring vigorously to obtain a white precipitate uniformly coated with calcium carbonate; completely dissolving 1.4 g of high-temperature coal tar pitch in 100 mL of toluene to obtain a solution of isotropic asphalt, adding 1 g of white precipitate to the solution, stirring for 24 h and then filtering, washing the precipitate with deionized water and drying; placing the dried precipitate in a tubular furnace, pre-oxidizing at 320° C. in an air atmosphere for 2 h, and carbonizing at 1000° C. in an argon atmosphere for 2 h to obtain a carbonized product; wherein the heating rate during the pre-oxidation process is 1° C. / min;
[0043] (5) The carbonized product is placed in 0.1 mol / L hydrochloric acid, washed thoroughly to remove calcium carbonate precipitate, then washed with deionized water until neutral, and dried to obtain a "carbon-void-silicon-carbon" four-level core-shell crystal domain petroleum coke-based silicon-carbon composite electrode material B; wherein the thickness of the silicon layer is 0.18 μm, the thickness of the void structure is 0.8 μm, and the thickness of the amorphous carbon layer is 0.8 μm.
[0044] Embodiment 3:
[0045] This embodiment provides a modification preparation method of a crystal domain petroleum coke-based silicon-carbon composite electrode material, comprising the following specific steps:
[0046] (1) grinding the crystal domain petroleum coke, sieving it through a 1000 mesh sieve, taking 1 g of the crystal domain petroleum coke particles and adding them into 200 mL of a 3 mol / L trichloroacetic acid solution, activating and stirring them at 200° C. for 24 h, and obtaining activated crystal domain petroleum coke particles;
[0047] (2) Dispersing the activated crystalline petroleum coke particles in deionized water, ultrasonicating for 1 hour, then dropwise adding 30 mL of 0.01 g / mL 3-tert-butyldimethylsilyl-2-propyn-1-ol ethanol solution, and continuing ultrasonic dispersion for 1.5 hours until completely dispersed; transferring the dispersion to a hydrothermal reactor, reacting at 160° C. for 8 hours; filtering the product of the hydrothermal reaction, washing the precipitate with ethanol and deionized water three times respectively, and drying it in an oven at 80° C. for 24 hours; obtaining a dried product;
[0048] (3) 1 g of the dried product was mixed with 0.1 g of magnesium powder and placed in a stainless steel reactor, and reacted at 600° C. for 6 h under an argon atmosphere. The product was then washed with 0.5 mol / L dilute hydrochloric acid, ethanol and deionized water until neutral, and vacuum dried at 100° C. for 24 h to obtain a treated magnesium thermal reaction product;
[0049] (4) Ultrasonic dispersion of the treated magnesium thermal reaction product in deionized water, and sequentially adding 1.5 g of sodium carbonate and 1.8 g of calcium chloride, stirring vigorously to obtain a white precipitate uniformly coated with calcium carbonate; completely dissolving 1.5 g of high-temperature coal tar pitch in 100 mL of toluene to obtain a solution of isotropic asphalt, adding 1 g of white precipitate to the solution, stirring for 24 h and then filtering, washing the precipitate with deionized water and drying; placing the dried precipitate in a tubular furnace, pre-oxidizing at 320° C. in an air atmosphere for 2 h, and carbonizing at 1000° C. in an argon atmosphere for 2 h to obtain a carbonized product; wherein the heating rate during the pre-oxidation process is 1° C. / min;
[0050] (5) The carbonized product is placed in 0.1 mol / L hydrochloric acid, washed thoroughly to remove calcium carbonate precipitate, then washed with deionized water until neutral, and dried to obtain a "carbon-void-silicon-carbon" four-level core-shell crystal domain petroleum coke-based silicon-carbon composite electrode material C; wherein the thickness of the silicon layer is 0.2 μm, the thickness of the void structure is 1 μm, and the thickness of the amorphous carbon layer is 1 μm.
[0051] Embodiment 4:
[0052] This embodiment provides a modification preparation method of a crystal domain petroleum coke-based silicon-carbon composite electrode material, comprising the following specific steps:
[0053] (1) grinding the crystal domain petroleum coke, sieving it through a 1000 mesh sieve, taking 1 g of the crystal domain petroleum coke particles and adding them into 200 mL of a 3 mol / L trichloroacetic acid solution, activating and stirring the solution at 200° C. for 24 h, and obtaining activated crystal domain petroleum coke particles;
[0054] (2) The activated crystalline petroleum coke particles were dispersed in deionized water, ultrasonicated for 1 hour, and then 30 mL of 0.01 g / mL 3-tert-butyldimethylsilyl-2-propyn-1-ol ethanol solution was added dropwise, and ultrasonic dispersion was continued for 1.5 hours until it was completely dispersed; the dispersion was transferred to a hydrothermal reactor and reacted at 160° C. for 8 hours; the product of the hydrothermal reaction was filtered, and the precipitate was washed three times with ethanol and deionized water respectively, and dried in an oven at 80° C. for 24 hours to obtain a dried product;
[0055] (3) 1 g of the dried product was mixed with 0.1 g of magnesium powder and placed in a stainless steel reactor, and reacted at 600° C. for 6 h under an argon atmosphere. The product was then washed with 0.5 mol / L dilute hydrochloric acid, ethanol and deionized water until neutral, and vacuum dried at 100° C. for 24 h to obtain a precipitate of magnesium thermal reaction;
[0056] (4) 1.2 g of high-temperature coal tar pitch was completely dissolved in 100 mL of toluene to obtain a solution of isotropic asphalt, 0.8 g of the precipitate from the magnesium thermal reaction was added to the solution, stirred for 24 h, filtered, washed with deionized water, and dried;
[0057] (5) The dried precipitate is placed in a tubular furnace, pre-oxidized at 320°C in an air atmosphere for 2 h, and carbonized at 1000°C in an argon atmosphere for 2 h; wherein the heating rate during the pre-oxidation process is 1°C / min; and a "carbon-silicon-carbon" three-level core-shell crystalline petroleum coke-based silicon-carbon composite electrode material D is obtained; wherein the thickness of the silicon layer is 0.2 μm, and the thickness of the amorphous carbon layer is 1 μm.
[0058] Embodiment 5:
[0059] This embodiment provides a modification preparation method of a petroleum coke-based silicon-carbon composite electrode material. The raw material petroleum coke used is Grade I petroleum coke that complies with GB / T 24533-2019, and its technical indicators are shown in Table 1.
[0060] Table 1 Main technical indicators of Grade I petroleum coke
[0061]
[0062] The specific steps include:
[0063] (1) Crush petroleum coke, sieve through a 1000-mesh sieve, take 1 g of petroleum coke particles and add them into 200 mL of a 3 mol / L trichloroacetic acid solution, activate and stir at 200° C. for 24 h, and obtain activated petroleum coke particles;
[0064] (2) The activated petroleum pyrolysis particles were dispersed in deionized water, ultrasonicated for 1 hour, and then 30 mL of 0.01 g / mL 3-tert-butyldimethylsilyl-2-propyn-1-ol ethanol solution was added dropwise, and ultrasonic dispersion was continued for 1.5 hours until it was completely dispersed; the dispersion was transferred to a hydrothermal reactor and reacted at 160° C. for 8 hours; the product of the hydrothermal reaction was filtered, and the precipitate was washed three times with ethanol and deionized water respectively, and dried in an oven at 80° C. for 24 hours; and the dried product was obtained;
[0065] (3) 1 g of the dried product was mixed with 0.1 g of magnesium powder and placed in a stainless steel reactor, and reacted at 600° C. for 6 h under an argon atmosphere. The product was then washed with 0.5 mol / L dilute hydrochloric acid, ethanol, and deionized water until neutral; and vacuum dried at 100° C. for 24 h to obtain a magnesium thermal reaction product;
[0066] (4) Ultrasonic dispersion of the treated magnesium thermal reaction product in deionized water, and sequentially adding 1.5 g of sodium carbonate and 1.8 g of calcium chloride, stirring vigorously to obtain a white precipitate uniformly coated with calcium carbonate; completely dissolving 1.5 g of high-temperature coal tar pitch in 100 mL of toluene to obtain a solution of isotropic asphalt, adding 1 g of white precipitate to the solution, stirring for 24 h and then filtering, washing the precipitate with deionized water and drying; placing the dried precipitate in a tubular furnace, pre-oxidizing at 320° C. in an air atmosphere for 2 h, and carbonizing at 1000° C. in an argon atmosphere for 2 h to obtain a carbonized product; wherein the heating rate during the pre-oxidation process is 1° C. / min;
[0067] (5) The carbonized product is placed in 0.1 mol / L hydrochloric acid, washed thoroughly to remove calcium carbonate precipitate, then washed with deionized water until neutral, and dried to obtain a "carbon-void-silicon-carbon" four-level core-shell type petroleum coke-based silicon-carbon composite electrode material E, wherein the thickness of the silicon layer is 0.2 μm, the thickness of the void structure is 1 μm, and the thickness of the amorphous carbon layer is 1 μm.
[0068] Example 6: Battery performance test
[0069] 1. Electrode preparation: The electrode materials prepared in Examples 1-5 were mixed with acetylene black and PVDF in a mass ratio of 8:1:1, NMP (nitromethylpyrrolidone) was used as a solvent, ground to form a uniform slurry and applied on a copper foil, dried at 90°C in vacuum for 24 hours, and rolled to obtain an electrode sheet.
[0070] 2. Battery performance test: The obtained electrode sheet was cut into a diameter of 12mm for battery assembly. The assembly process was carried out in a glove box filled with argon, and the water and oxygen content was less than 0.01ppm. The battery used a CR2032 button cell, with a metal lithium sheet as the counter electrode, a polypropylene film as the diaphragm, and 1M lithium hexafluorophosphate (the solvent was a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, with 5% fluoroethylene carbonate added) as the electrolyte. The assembled button cell was subjected to a 0.1C charge and discharge cycle performance test and a 10C high current discharge performance test at 25°C and a voltage range of 0.05V-2.2V. The measured battery first cycle specific capacity (mAh / g), first charge and discharge efficiency (%), and reversible cycle specific capacity (mAh / g, 500 cycles) were recorded, and the silicon content in each electrode material was given. The results are shown in Table 2.
[0071] Table 2 Comparison of electrode material performance
[0072]
[0073] It can be seen from the data in the table that compared with the existing graphite negative electrode (360mAh / g), the silicon-carbon composite electrode materials A, B and C prepared by the method described in Examples 1-3 of the present invention all have higher charge and discharge cycle performance (all above 580mAh / g). In addition, by comparison, it can be found that the first-cycle coulomb efficiency of the battery increases with the increase of the silicon content in the electrode material, but the first-cycle specific capacity shows a trend of first increasing and then decreasing with the increase of the silicon content. This is because the increase in the proportion of silicon increases the capacity it provides. However, due to the huge volume expansion of the silicon material, an excessively high silicon content will cause the specific capacity to decay. Therefore, electrode material B has the best performance, and its silicon content of 7.1wt% is the best.
[0074] The electrode material D prepared in Example 4 does not introduce a void structure, and its reversible cycle specific capacity is significantly lower than that of Examples 1-3, indicating that the void structure is well formed in the electrode materials A, B and C, which effectively alleviates the volume expansion of silicon inside the composite material.
[0075] In Example 5, Grade I petroleum coke in accordance with GB / T 24533-2019 is used as the raw material. The first-cycle coulomb efficiency and reversible cycle specific capacity are lower than those in Examples 1-3, indicating that the coexistence and uniform distribution of the needle-domain, wide-domain and mosaic polarization structures in the crystalline petroleum coke can ensure that the material has good cycle stability, rate performance and reversible capacity, and provides a large number of active sites for silicon connection. In addition, by controlling the amount of sodium carbonate and calcium chloride added, different thicknesses of void layers can be prepared, which can be flexibly adjusted according to different silicon loadings.
Claims
1. A modification and preparation method of a crystalline petroleum coke-based silicon-carbon composite electrode material, characterized in that: The following steps are involved: Step 1: using crystal domain petroleum coke as a raw material, crushing it and then sieving it with a 600-1000 mesh screen to obtain crystal domain petroleum coke particles; adding the crystal domain petroleum coke particles to an organic acid solution with a concentration of 3-5 mol / L, stirring at 180-230° C. for 24 hours, to obtain activated crystal domain petroleum coke particles; the polarization structure of the crystal domain petroleum coke consists of a needle domain, a wide domain and a mosaic structure, and the three polarization structures coexist and are evenly distributed and mixed; Step 2: Ultrasonic dispersion of activated crystalline petroleum coke particles in deionized water, then dropwise addition of oxygen-containing organosilicon compound, and continued ultrasonication until complete dispersion; transfer the dispersion to a hydrothermal reactor, and react at 160-200° C. for 6-15 hours; filter the product of the hydrothermal reaction, wash the precipitate with ethanol and deionized water three times respectively, and dry it in an oven to obtain a dried product; Step 3: Mix the dried product with magnesium powder and place it in a stainless steel reactor, and perform magnesium thermal reaction at 600° C. for 4-8 hours under argon atmosphere; wash the product of magnesium thermal reaction with dilute hydrochloric acid, ethanol and deionized water respectively until neutral to obtain a treated magnesium thermal reaction product; Step 4: Ultrasonic dispersion of the treated magnesium thermal reaction product in deionized water, adding sodium carbonate and calcium chloride in turn, stirring vigorously to obtain a white precipitate uniformly coated with calcium carbonate; then adding the white precipitate to a solution of isotropic asphalt, stirring for 24 hours and filtering, washing the precipitate with deionized water and drying; placing the dried precipitate in a tubular furnace, pre-oxidizing at 320°C in an air atmosphere for 2-4 hours, and carbonizing at 800-1200°C in an argon atmosphere for 2 hours to obtain a carbonized product; Step 5: Place the carbonized product in 0.1 mol / L hydrochloric acid, wash thoroughly to remove calcium carbonate precipitate, then wash with deionized water until neutral, and dry to obtain a "carbon-void-silicon-carbon" four-level core-shell crystal domain petroleum coke-based silicon-carbon composite electrode material.
2. The modification preparation method of a crystalline petroleum coke-based silicon-carbon composite electrode material according to claim 1, characterized in that: In the polarization structure of the crystalline petroleum coke, the size of the needle-domain and wide-area polarization structures is 50-500 μm, accounting for 70%-85% of the total area, and the size of the mosaic polarization structure is 1-50 μm, accounting for 15%-30% of the total area.
3. The modification preparation method of a crystalline petroleum coke-based silicon-carbon composite electrode material according to claim 1, characterized in that: The organic acid comprises trichloroacetic acid or p-toluenesulfonic acid; the oxygen-containing organosilicon compound is selected from one of triisopropylsilyl trifluoromethanesulfonate, 3-tert-butyldimethylsilyl-2-propyn-1-ol or (1,1-dimethylethyl)dimethylsilyl trifluoromethanesulfonate.
4. The modification preparation method of a crystalline petroleum coke-based silicon-carbon composite electrode material according to claim 1, characterized in that: The isotropic asphalt is coal-based coated asphalt, petroleum-based coated asphalt or high-temperature coal tar with a softening point of 100-200°C. The solution preparation method of the isotropic asphalt is to dissolve the isotropic asphalt in a solvent, and the solvent is selected from one or more of tetrahydrofuran, toluene, N-methylpyrrolidone, and pyridine; the dosage ratio of the solvent to the isotropic asphalt is 100mL: (1-1.5)g.
5. The modification preparation method of a crystalline petroleum coke-based silicon-carbon composite electrode material according to claim 1, characterized in that: The dosage relationship of the crystal domain petroleum coke particles, organic acid solution and oxygen-containing organosilicon compound is 1g: 200mL: (0.1-0.5) g; The dried product obtained in step 2, magnesium powder, sodium carbonate and calcium chloride are used in a ratio of 1 g: 0.1 g: (1-1.5) g: (1.2-1.8) g; In step 4, the ratio of white precipitate to isotropic asphalt is 1 g:(1-1.5) g.
6. The crystalline petroleum coke-based silicon-carbon composite electrode material prepared by the method according to any one of claims 1 to 5, characterized in that: The crystalline petroleum coke-based silicon-carbon composite electrode material has a four-level core-shell structure of "carbon-void-silicon-carbon", with a silicon layer thickness of 0.1-0.2 μm, a void structure thickness of 0.3-1 μm, and an amorphous carbon layer thickness of 0.5-1 μm.
Citation Information
Patent Citations
Silicon-carbon composite material and preparation method thereof, and lithium ion battery
CN103337613A
Low-cost preparing method of silicon and carbon compound cathode material for lithium ion battery
CN104362315A